Detecting the Development of Land Use Patterns for Building in Urban Areas by Using High Resolution Image - A Amar (TATALOKA, 2013)
This study aimed at obtaining factual information and overview to the development of land use patterns for buildings in urban areas by interval time period, both spatially and aspatially, by utilizing high-resolution satellite photo image (high resolution spatial image) combined with field observations. This research used survey method approach. The data of this study consisted of primary and secondary data classified into spatial and aspatial data in the form of time series obtained through documents recording techniques, field observations, previous mapping sources, as well as depth interviews. The analysis technique used Image Processing Analysis through programs and software Arc View. The result of research showed that there was a quite rapid development of land use patterns for building in Palu within the last 50 years (≤ 1970 till 2010) It had building addition in 65,173 units (82.28%), from 14,032 units in ≤1970 to 79,205 units in 2010, and the addition of extensive use of land for building was 4723.52 ha (89.06%), from 516.98 ha in ≤ 1970 to 4723.52 ha in 2010. The development level of land use patterns for building was getting along with the size of distribution and population growth in Palu.